Penerapan permainan tradisional congklak lidi sebagai media membangun karakter anak sekolah dasar - Iswinarti Iswinarti; Putri Saraswati (Altruis: Journal of Community Services, 2022)
Character building of children basically aims to educate children to have the best performance and be moral. Traditional games are inherited and contain noble values. Traditional games contain values that can be used as media to build children's character. The Congklak Lidi game is a traditional game that contains high values for characters such as morals, problem-solving, and self-control. The problem of this activity partner was the unavailability of facilities, infrastructure, and resources to implement these traditional games. The purpose of this program was to apply the traditional game of Congklak Lidi to elementary school children in order to install positive values to build children's character, such as problem-solving, unyielding spirit, self-control, and honesty. The Congklak Lidi game program was applied to 29 children aged 6-12 years (grades 1st – 6th). The program was planned to be implemented in partner schools, but due to the Covid-19 pandemic, the implementation was carried out in several areas in East Java according to the area of origin of each facilitator. The result of this program is the congklak lidi can be implemented at home hence the children’s characters can be learned.